Robot-Assisted Lung Biopsy: A Safer Approach to Lung Lesions - Maqsood, Shadab; Khan, Tahir Ahmad; Hussain, Manzoor; Bhat, Mudasir; Shera, Tahleel Altaf; Gojwari, Tariq Ahmad; Shaheen, Feroze A. (Journal of Clinical Interventional Radiology ISVIR, 2023)
Purpose This article evaluates the feasibility, safety, and technical success of robot-assisted computed tomography (CT)-guided percutaneous lung biopsy.Methods CT-guided lung biopsy was performed after clearance from the institutional ethical committee in 60 patients who were assigned to two groups, group A (robot-assisted biopsy) and group B (conventional CT-guided biopsy). The accuracy of needle placement, number of needle adjustments, radiation dose, procedure time, and complications were compared in both these groups.Results In group A, the procedure duration was significantly shorter (p = 0.001), dose length product, lower (p = 0.001), accuracy of needle placement, superior (p = 0.003), and complication rates were lower (p = 0.002) compared with conventional CT guidedbiopsy.Conclusion Robotic assistance during CT lung biopsy is associated with improved targeting of lesions with more diagnostic yield and less procedure duration, radiation exposure, and fewer complications compared with conventional CT lung biopsy.
Keywords: CT-guided lung biopsy; robotic biopsy; lung cancer; interventional radiology